Interaction of blood-entry components, network pharmacology and transcriptomics to elucidate the mechanism of Wentong plaster in treating primary dysmenorrhea - Zongtong Yang; Ziqi Jiao; Cheng Wang; Xiaojing Li; Mengyu Yuan; Zaiyun Sui; Wenhui Wang; Wenjing Hou (Frontiers in Pharmacology, 2025)
IntroductionPrimary dysmenorrhea (PD) is characterized by pain during the menstrual cycle, affects women's health. Our group developed a traditional Chinese medicine plaster (Wentong plaster, WTT) for the treatment of PD. However, the underlying mechanisms have not yet been elucidated.MethodsIn this study, the blood-entry components of WTT were detected using UPLC-Q-Exactive Orbitrap-MS, and the therapeutic functions of WTT on PD were evaluated by the writhing response, pathological analysis, and the levels of estrogen, nitric oxide, progesterone, among other indicators. Network pharmacology and transcriptomics were used to elucidate the underlying mechanisms. Finally, enzyme-linked immunosorbent assay and western blotting were used to determine the levels of relevant indicators.ResultsOur findings indicate that 49 original blood-entry components were detected. Meanwhile, WTT upregulated the level of NO, and downregulated the levels of PGF2α, PGE2, estrogen, and progesterone, thereby increasing blood flow, alleviating inflammatory responses, and inhibiting the writhing response. Results from network pharmacology and transcriptomics analyses indicated that WTT could increase the expression of Lcn2 and decrease the expression of Cxcl6 and IL-17, thereby regulating the IL-17 signaling pathway, and alleviating inflammation to treat PD.ConclusionWTT mainly down-regulates the levels of Cxcl6 and IL-17 and up-regulates the expression of Lcn2, further regulates the IL-17 signaling pathway to alleviate inflammation, ultimately treating PD. This study provides a basis for further research on the mechanism of WTT, and offers a reference for its clinical application.